The social contagion of incremental and entity trait beliefs. (1st April 2017) - Burkley, Edward; Curtis, Jessica; Hatvany, Thomas
Abstract: This study examined if people's own beliefs regarding the malleability of traits is influenced by the beliefs of surrounding others. Consistent with the idea of social contagion, people who read a vignette of someone espousing an incremental view (i.e., perceive traits as malleable) were more likely to endorse an incremental view themselves than those who read a vignette of someone with an entity view (i.e., perceive traits as fixed). Results indicated this contagion effect is not domain specific and can spread from one skill domain (e.g., athletics) to another (e.g., mathematics). Furthermore, others who espoused an incremental view were perceived to be more inspiring and therefore more likely to serve as positive role models than those who espoused an entity view. Overall, these results provide a bridge between the largely disparate literature areas of implicit trait beliefs, social contagion, and role models and indicate one potential source for the origination of these trait beliefs. Highlights: Examined effect if incremental and entity beliefs are socially contagious. People adopted incremental view after exposure to incremental other. This contagion effect spread from one domain to another (not domain specific). The incremental other was more likely to serve as role model than the entity other. This work bridges literatures on trait beliefs, social contagion and role models.